Polynomial and multivariate mapping-based triple-key approach for secure key distribution in wireless sensor networks. (April 2017) - A., Selva Reegan; E., Baburaj
Abstract: Distribution of cryptographic key plays a vital role to improve the security and integrity in Wireless Sensor Networks (WSN). Due to high resilience to the attacks, the pairwise key distribution schemes are highly preferred than other schemes. However, due to the resource constraints on the nodes and the threat of node capture, pairwise key establishment in the sensor networks is a challenging task. The security performance of these schemes decreases with the increase in the number of compromised nodes. To overcome these issues, a Polynomial and Multivariate Mapping-Based Triple-Key (PMMTK) distribution approach is proposed in this paper. It involves calculation of individual key of the nodes and common triple-key. Our proposed method achieves higher data freshness, throughput, average number of clusters, overall network lifetime, network connectivity, better packet delivery ratio and lower end-to-end delay, average number of key establishment and total authentication overhead.